Comparative Growth and Nutrient Utilization in Lambs and Kids Fed With Pala (Ziziphus Nummularia Leaves) - Mali, P C; Bedekar, A R; Patnayak, B C (Annals of Arid Zone, 2016)
Eight lambs and 8 kids were divided into two groups (4 in each) and fed on Pala (Ziziphus nummularla leaves) ad lib either alone or supplemented with a mineral mixture (Milkkmin', Sarabhai Chemicals) free choice for a period of 210 days.The daily gain of lambs fed on Pala alone or Pala supplemented with a mineral mixture over a period of 210 days was 51.0 and 38.0 g, respectively. The corresponding values for kids were 76.0 and 64.0 g. Average daily feed consumption over the whole experimental period ranged from 1.230 to 1.282 kg in all four groups but the consumption per unit weight was higher in kids than in lambs. Within species mineral mixture supplemental ion had a rather depressing effect on weight gain. In lambs, low weight gain appeared to be due to low intake of DCP in relation to TDN as compared to kids. The average dry matter intake during the digestion trial was 3.4 Â± 0.1 and 3.8 Â± 0.2 kg per 100 kg body weigh I for lamhs and k ids respectively. In general, the digestibility coefficient of nutrients was higher in kids than in lambs. In both the species, however,protein digesti bility was low although kids showed higher digestibility than lambs (23. and 29% for lambs and 35 and 38% for kids). In lambs nitrogen excreted in faeces was 70 to 77% of the intake as compared to 62 to 65% in kids. Urinary nitrogen excretion was 14 to 17% of the intake in both the species. It is concluded that in a Pala feeding regime kids perform better and utilize nutrients better than lambs although both the species could show growth.